On Codes Over Mixed Finite Ring ℤ₂ℤ₄ and its Related Parameter - Pandian , P. Chella (Journal of Nepal Mathematical Society, 2025)
In this paper, we have to find out the lower bound and upper bound of some class codes in the finite ring ℝ = ℤ₂ + u ℤ₂ + u² ℤ₂ where u³ = 0, with Gray Mapping ℝ → ℤ₂ ℤ₄ with respect to different weight by using covering radius. Also, the covering radius of various lengths and different lengths of the Block Repetition Codes in the finite ring ℝ is determined.